2019
DOI: 10.3389/fphys.2019.00324
|View full text |Cite
|
Sign up to set email alerts
|

CXCR2 Blockade Mitigates Neural Cell Injury Following Preclinical Chorioamnionitis

Abstract: Minimizing central nervous system (CNS) injury from preterm birth depends upon identification of the critical pathways that underlie essential neurodevelopmental and CNS pathophysiology. While chorioamnionitis (CHORIO), is a leading cause of preterm birth, the precise mechanism linking prenatal brain injury and long-term CNS injury is unknown. The chemokine (C-X-C motif) ligand 1 (CXCL1) and its cognate receptor, CXCR2, are implicated in a variety of uterine and neuropathologies, however, their role in CNS inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 96 publications
1
32
0
Order By: Relevance
“…In the presence of neuroinflammation, CXCL1 and CXCR2 are upregulated rapidly ( Carlson et al, 2008 ; Kerstetter et al, 2009 ; Kielian et al, 2001 ; Liu et al, 2010 ; Roy et al, 2012 ). Studies in neonatal brain injury and in adult neurodegenerative disorders have shown that inhibiting the CXCR2 receptor is neuroprotective and can attenuate white matter and axonal injury ( Yellowhair et al, 2019 ). This neuroprotective effect is felt to be related to a decrease in neutrophil infiltration in the brain ( Yellowhair et al, 2018 , 2019 ) which is often a secondary response following injury and can exacerbate the initial injury.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of neuroinflammation, CXCL1 and CXCR2 are upregulated rapidly ( Carlson et al, 2008 ; Kerstetter et al, 2009 ; Kielian et al, 2001 ; Liu et al, 2010 ; Roy et al, 2012 ). Studies in neonatal brain injury and in adult neurodegenerative disorders have shown that inhibiting the CXCR2 receptor is neuroprotective and can attenuate white matter and axonal injury ( Yellowhair et al, 2019 ). This neuroprotective effect is felt to be related to a decrease in neutrophil infiltration in the brain ( Yellowhair et al, 2018 , 2019 ) which is often a secondary response following injury and can exacerbate the initial injury.…”
Section: Discussionmentioning
confidence: 99%
“…By Multiplex and immunohistochemistry analysis, we were able to show that highly activated factors in APOE4 injured mice include CXCL1, Il-6, TNF-α, and microglia. CXCL1 is a cytokine that is a ligand for the CXCR2 receptor, whose activation has been implicated in increased pain after injury 77 and blockade has been shown to reduce neuroinflammation after injury 78 . Il-6 is an important pro-inflammatory interleukin.…”
Section: Discussionmentioning
confidence: 99%
“…Ystgaard et al found different distribution of NLRP3 gene upregulation in their newborn mouse model 24 h post hypoxic-ischemic injury, with a significant upregulation in the hippocampus and thalamus ( 35 ). Yellowhair et al showed that CXCL1/CXCR2 signaling contributes to newborn brain inflammation in an in-vitro model of preclinical chorioamnionitis and that blocking the CXCR2 receptor reduces neuroinflammation in different white matter regions ( 36 ). Interestingly in our study, we found a gender-specific upregulation of CXCL1 protein level in males in the LPS/HI group compared with the Sham group in the cortex ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%